Wetting-induced collapse of loess: Tracing microstructural evolution - Wang, Yuanyuan; Li, Yanrong (Engineering geology, 2024)
Loess is a silt-dominated, clastic yellow-to-yellowish brown aeolian sediment with high porosity and low density. The metastable microstructure of loess makes it highly susceptible to collapse, which plays a major role in landform evolution, geohazard development and engineering damages, particularly the widespread occurrences of settlement, deformation and cracking of civil engineering structures. Differing from the existing investigations based on pre- and post-collapse comparison, the present study is to report the microstructural changes during the collapse process and to determine how each microstructural constitutive element participates in this process. A series of laboratory tests was conducted on undisturbed loess specimens to simulate and capture snapshots of microstructure at five representative points during the entire collapse process. Results show that the loess microstructure becomes more homogeneous as the outstanding macropores are crushed into smaller (meso- and mini-pores) pores, the number of pores is dramatically increased, and the pore throats become narrower. The pore shapes have no obvious changes and remain elongated and rough-edged morphology from the point of view of statistic. Regarding solids, the pre-collapse unstable point-to-point contacts tend to transform into relatively stable edge (edge-edge or point-edge) type contacts, whilst coarse particles tend to reorient along the horizonal direction. XRD, SEM and EDS analysis indicates that these changes in the nature and distribution of pores and particles result from (1) the breakage and disintegration of moderately to highly weathered particles, (2) the disintegration of the matrix due to the swelling of clay minerals and the dissolution of calcium carbonates, (3) the consequential modifications of the microscopic forces which lead to slipping, rotation and therefore dislocation of particles, and (4) the collapse of mesoscale force chains along particles, reforming on smaller scales with larger numbers, shorter lengths and horizontal alignments. [Display omitted] •Systematic experimental microstructural study of wetting-driven loess collapse.•Tracing collapse mechanism with microstructure and roles of its elements.•Loess collapse results essentially from crushing of its macropores (> 32 μm).•Matrix changes with fragmentation, dissolution and swelling of the solids.•Particle force chains break as particles disintegrate, dislocate and/or rotate.